PERAN GURU BIMBINGAN DAN KONSELING TERHADAP PERILAKU BELAJAR SISWA KELAS IX SMP NEGERI 1 SIDOHARJO - nuriah halleyda; Murdiasih Anggraini (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
Guidance and counseling is a school component that provides counseling services to students. One of the duties of the guidance and counseling teacher/counselor is to help develop students' potentials in a positive direction, including having good study habits. The purpose of this study was to investigate the influence of the guidance and counseling teacher's role on the learning behavior of class IX students at SMP Negeri 1 Sidoharjo. The method used is quantitative with a correlation approach. From the simple linear regression statistical test with SPSS which was carried out, the result was that the correlation value (R) was 0.129. From this output, the coefficient of determination (R square) is 0.17, which implies that the effect of the independent variable (the role of the guidance and counseling teacher) on the dependent variable (learning behavior) is 1.7%, the calculated F value = 2.227, with a significance level of > 0.05, so it can be concluded that there is no influence of the role of the counseling teacher on student learning behavior. Thus, the first hypothesis in this study can be rejected.